2007
DOI: 10.1159/000101995
|View full text |Cite
|
Sign up to set email alerts
|

β1 Integrins Mediate Tubule Formation Induced by Supernatants Derived from KSHV-Infected Cells

Abstract: Objective: Angiogenesis is defined as the formation of new blood vessels. In a recently concluded study, we identified Kaposi’s sarcoma-associated herpesvirus (KSHV)-infected cells derived from primary effusion lymphoma (PEL) to overexpress vascular endothelial growth factor (VEGF) that had the propensity to mediate tubule formation on a Matrigel, an indicator of angiogenesis. The objective of this study was to determine the receptor molecules that mediate the tubule formation induced by the supernatant derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 68 publications
2
13
0
Order By: Relevance
“…These activities are necessary for vascularization of solid tumors and contribute to the promotion of tumor formation and metastasis. As has been described by others, KSHV is likely to promote angiogenesis in a paracrine fashion to promote new blood vessel growth in the KS tumor [10], [12], [19][21], [28], [41], [59]. Here we found that KSHV also directly induces angiogenic phenotypes in latently infected cells.…”
Section: Discussionsupporting
confidence: 85%
“…These activities are necessary for vascularization of solid tumors and contribute to the promotion of tumor formation and metastasis. As has been described by others, KSHV is likely to promote angiogenesis in a paracrine fashion to promote new blood vessel growth in the KS tumor [10], [12], [19][21], [28], [41], [59]. Here we found that KSHV also directly induces angiogenic phenotypes in latently infected cells.…”
Section: Discussionsupporting
confidence: 85%
“…Quantitative RT-PCR (qRT-PCR)-The qRT-PCR was performed using the synthesized cDNA in a 25-l reaction volume to analyze the expression of ORF50, egr-1, and ␤-actin as per earlier protocols (24). (25).…”
Section: Cells-hmvec-d Cells Were Propagated In Egmmentioning
confidence: 99%
“…The gB-and gL-positive cells were sorted using a flow cytometer based on the expression of GFP. The time at which the mixture of cells was seeded onto 12-well plates was considered as 0 h. At different time points (1,4,8,12,24,48,72,96, and 120 h) post-seeding, the cells were lysed, RNA was extracted, cDNA was prepared, and the expression of ORF50 was monitored by qRT-PCR using specific primers. The relative copy numbers of the ORF50 transcripts were calculated from the standard graph plotted using the Ct values for different dilutions of in vitro transcribed ORF50 (using ORF50/pGEM-T plasmid).…”
Section: Kshv Infection Of Hmvec-d Cells-hmvec-d Cells Were Infected mentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] It was shown that KSHV-infected cells secrete VEGF and induce in vitro angiogenesis. 30 Recent studies reported that b-integrins 31 or induction of angiopoietin-2 32 mediates PEL-induced tube formation. Cells influence their immediate microenvironment either through paracrine mechanisms or through direct cell-cell interaction, such as adhesion and gap junction-mediated communication.…”
Section: Introductionmentioning
confidence: 99%